2015
DOI: 10.1016/j.ejmech.2014.12.050
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, anticancer activity and molecular docking studies on a series of heterocyclic trans-cyanocombretastatin analogues as antitubulin agents

Abstract: A series of heterocyclic combretastatin analogues have been synthesized and evaluated for their anticancer activity against a panel of 60 human cancer cell lines. The most potent compounds were two 3,4,5-trimethoxy phenyl analogues containing either an (Z)-indol-2-yl (8) or (Z)-benzo[b]furan-2-yl (12) moiety; these compounds exhibited GI50 values of <10 nM against 74% and 70%, respectively, of the human cancer cell lines in the 60-cell panel. Compounds 8, and 12 and two previously reported compounds in the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…U-251 MG is an established GBM cell line [ 15 ], part of the NCI-60 human cancer cell lines [ 25 ], with the ability to form spheroids with invasive properties [ 26 ]; it has been used in the screening of pharmaceutical agents to identify, characterize, and select novel compounds with growth inhibition and/or killing of tumor cells. A series of 22 different compounds called BS, BSK, JVM PNR, and ST [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ] whose the chemical structures, details, and activity are explained in Table 1 and Figure S1 , were incubated with the spheroids for 48 h to define the toxicity the effects on their invasiveness. These compounds have anti-invasive properties, as they interfere with pathways of cell invasion ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…U-251 MG is an established GBM cell line [ 15 ], part of the NCI-60 human cancer cell lines [ 25 ], with the ability to form spheroids with invasive properties [ 26 ]; it has been used in the screening of pharmaceutical agents to identify, characterize, and select novel compounds with growth inhibition and/or killing of tumor cells. A series of 22 different compounds called BS, BSK, JVM PNR, and ST [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ] whose the chemical structures, details, and activity are explained in Table 1 and Figure S1 , were incubated with the spheroids for 48 h to define the toxicity the effects on their invasiveness. These compounds have anti-invasive properties, as they interfere with pathways of cell invasion ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…BITC was the most potent growth inhibitor with half-maximum IC50 values on HeLa, Fem-x and LS 174 cells. Penthala et al (2015) reported that trans-cyanostilbene analogues which contained the 3,4,5-trimethoxyphenyl and dimethoxyphenyl moieties exhibited low micromolar growth inhibition against human cancer in the panel. Luo et al (2017) suggested that acetyl chloride-mediated creation of PEITC derivatives proves to be convenient and provides the expected excellent products yields.…”
Section: Resultsmentioning
confidence: 99%
“…Docking was performed using SwissDock (http://www.swissdock.ch/), based on the docking algorithm EADock DSS [27]. Docking was performed using protocols established in our previous studies [16]. Use of the most exhaustive and unbiased option in SwissDock ensured the sampling of the maximum number of binding modes for each molecule.…”
Section: In Silico Molecular Docking Studiesmentioning
confidence: 99%
“…The reaction mixture was stirred at room temperature for 2–3 hours for the reaction to complete and the final product to crash out of the solution. The precipitate is filtered, washed with water and dried to yield the final compounds with yields ranging from 70–95 % (Scheme 1) [16]. …”
Section: 0 Experimental Sectionmentioning
confidence: 99%